REFORMASI HUKUM DI BIDANG KEKAYAAN INTELEKTUAL UNTUK MENGANTISIPASI PELANGGARAN MEREK MELALUI NAMA DOMAIN (CYBERSQUATTING) - Astrini, Widiya Murti; Ratnawati, Elfrida (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The article was written with the purpose of examining protection for registered trademark owners who become the victims of cybersquatting crime legally. The problem is focused on the implications of Law Number 20 of 2016 concerning Trademarks and Geographical Indications regarding the handling of cybersquatting cases in Indonesia. To approach this problem, the legal certainty theory is used as a reference. This study uses a type of normative legal research with secondary data which is analyzed qualitatively. The results of the study concluded that Law Number 20 of 2016 has not clearly explained and regulated cybersquatting, so it will be difficult to ensnare the perpetrators. Therefore, the government needs to formulate special regulations governing cybersquatting so that in the future it can provide legal certainty to the public.